A historical baseline study of the páramo of Antisana in the Ecuadorian Andes including the impacts of burning, grazing and trampling. (3rd July 2020) - Grubb, Peter J.; Lloyd, J. Robert; Pennington, Terence D.; Páez-Bimos, Sebastián
ABSTRACT: Background: We report the vegetation at 4050–4600 m in 1960 on the western slopes of Antisana, Ecuador, decades before burning and grazing were prohibited. Aim : To provide a baseline against which new surveys could be compared to evaluate conservation efforts. Methods: We (a) ordinated grassland types and derived communities using constancy values of species in typical stands, (b) recorded evidence of community dynamics, (c) recorded the composition of communities occupying smaller areas than the grassy páramo, and (d) recorded inhibition and facilitation of other species by Azorella cushions. Results: Short-turf grassland had replaced much tall-tussock grassland as a result of grazing and burning. Intense trampling had resulted in dominance by an introduced annual grass. Disturbance of most tall-tussock grassland on lava flows had left gaps made by fire or rabbit-scratching; these were invaded by distinctive sets of species. Azonal communities, changed much less by humans, contained 63% of 155 native species of vascular plant encountered, and 68% of 65 mosses. Younger cushions of Azorella impacted negatively on associated species but older cushions had facilitative effects. Conclusions: Our study provides an adequate record against which to determine the extent and nature of changes in the vegetation since farming of livestock ceased.